Siblings' life aspirations in the context of Duchenne muscular dystrophy: a mixed-methods case-control study. - Schwartz, Carolyn E.; Biletch, Elijah.; Stuart, Richard B.; Rapkin, Bruce D. (Tufts University. Tisch Library., 2022)
Keywords: Duchenne muscular dystrophy, Aspirations, Goals, Siblings, Case-control, Mixed methods.; Springer Open.